Economic Growth in Canada and the United States: Supply‐Push or Demand‐Pull?. (15th August 2014) - Tang, Jianmin; Wang, Weimin
Abstract : Understanding the nature of structural change and the sources of economic growth of an economy, especially the relative importance of different industries, is essential for policy‐making. This paper estimates industry contribution to economic growth in both Canada and the United States. It argues that industry contribution should be evaluated on the basis of the performance of an industry in terms of creating economic value relative to other industries. In particular, it calls for the quantity and the price effects, which is consistent with real GDP in the chained‐Fisher index that values the industry more when its price rises and less when its price declines. This is an important departure from the traditional methodologies that consider only quantity effect. This paper shows that the contribution from demand‐driven industries is significantly more than the finding based on traditional thinking.